Estimation of probable maximum precipitation for tropical catchment - Sammen S.; Mohamed T.; Ghazali A.A.; Sideq L.; Aziz A.A. (EDP Sciences, 2023)
Catchments; Flood control; Precipitation (meteorology); Runoff; Duration curve; Extreme rainfall; Physical methods; Precipitation depths; Probable maximum floods; Probable maximum precipitation; Return periods; Statistical approach; Construction